TUGAS DAN FUNGSI DINAS KESEHATAN KOTA SEMARANG DALAM MEMBERIKAN PELAYANAN JAMKESMAS, KHUSUSNYA DI KECAMATAN TEMBALANG - Irma Cahyaningtias, Amiek Soemarmi, Budi Goetami (Diponegoro Law Journal, 2012)
Healthcare is a right, and investment, and all citizens are entitled to health care, including the poor and people in need.Needed a system that regulates the implementation for fulfilling the rights of citizens to obtain social welfare, the health services, because health is very important to perform an activity in order to earn a decent living, the Semarang City Health Office provide free medical treatment. Jamkesmas is the Community Health Insurance provided by the City of Semarang to the poor and people who are not able to certain conditions, the study entitled "DUTIES AND FUNCTIONS OF THE DEPARTMENT OF HEALTH CITY SEMARANG JAMKESMAS PROVIDE SERVICES, ESPECIALLY IN AREAS District Tembalang ". The method used in this study is meant Juridical An Empirical studies conducted research exploring ways to view or positive law,namely the principles of law,regulations interrelated and appropriate by the rules law and researching in the field in order to obtain accurate data and the corresponding systematic laws, so researchers must conclude. From the research that the duties and functions of the Semarang City Health Department in providing services Jamkesmas is to improve health care for the poor and people who can not afford a fair and in accordance with the applicable procedures, so that there is no discrimination in obtaining health services, while the function is as a team managers in service delivery and as for Jamkesmaskot or Jamkesmas and constraints that affect the provision of Jamkesmas include membership, health care, finance, and organization, role and functions of local government and to overcome the operational and policy efforts.